The impact of fintech on sustainability performance through financial inclusion: A case study of MSME actors in Indonesia using diffusion of innovation theory (DIT) - Kolefiyan, Ihsyan (Trigin Publisher, 2026)
This study analyzes the role of Financial Technology (FinTech) in improving the sustainability performance of MSMEs in Indonesia by positioning financial inclusion as a mediating mechanism within the Diffusion of Innovation Theory (DIT) framework. Although various studies acknowledge the contribution of FinTech to business sustainability, the mechanisms explaining how FinTech adoption translates into sustainable performance achievements have not been empirically studied, especially in the context of MSMEs in developing countries. To fill this gap, this study uses a quantitative survey-based approach involving 205 MSME actors who use FinTech services in Indonesia. The data is analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between FinTech, financial inclusion, and sustainability performance. The results of the study indicate that FinTech has a positive and significant effect on financial inclusion and sustainability performance. In addition, financial inclusion also has a positive and significant effect on sustainability performance and acts as a significant mediator in the relationship between FinTech and sustainability performance. These findings indicate that FinTech will be more effective in promoting the sustainability of MSMEs if accompanied by the expansion of inclusive digital financial access. Theoretically, this study expands the application of DIT from merely explaining innovation adoption to understanding the performance implications of digital financial innovation. Practically, these findings emphasize the importance of strengthening an inclusive digital financial ecosystem to support the sustainability of MSMEs in Indonesia.